---
I'm not sure how to delete this question - I had an error in my calculations but I managed to figure it out and there's no point in keeping this question up anymore
---
I'm not sure how to delete this question - I had an error in my calculations but I managed to figure it out and there's no point in keeping this question up anymore
You perhaps have multiplied or subtracted incorrectly. $\displaystyle 2(x- 2)(x- 3)(x+ 5)= 2(x^2- 5x+ 6)(x+ 5)$$\displaystyle = 2(x^3-38x+ 30)= 2x^3- 38x+ 60= 120$ so that $\displaystyle 2x^3- 38x- 60= 0$, not "- 150". Dividing through by 2, $\displaystyle x^3- 19x- 30= 0$. I notice that $\displaystyle (-2)^3- 19(-2)- 30= -8+ 38- 30= 0$.